2002
DOI: 10.1002/1099-0682(200203)2002:4<943::aid-ejic943>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Three Novel End-to-End Single Azido-Bridged Ferromagnetic Copper(II) Chains: Synthesis, Crystal Structure, and Magnetic Behavior

Abstract: Three new single end‐to‐end azido‐bridged copper(II) chains [Cu(L1)(N3)]n(ClO4)n (1), [Cu(L2)(N3)]n(ClO4)n (2), and [Cu(L3)(N3)]n(ClO4)n (3) using three different tridentate Schiff bases L1, L2, and L3, obtained from condensation of pyridine‐2‐carbaldehyde with N,N‐dimethylethane‐1,2‐diamine, N,N‐diethylethane‐1,2‐diamine, and 4‐(2‐aminoethyl)morpholine, respectively, have been synthesized, and their crystal structures have been determined by X‐ray diffraction methods. Complex 1, C10H15CuN6ClO4, crystallizes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
32
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 38 publications
4
32
0
Order By: Relevance
“…This ligand has attracted much attention for two main reasons. First, the azide anion can behave as a bidentate bridging ligand (end-to-on, l 1,1 -N 3 ''EO'' [9][10][11], or end-to-end, l 1,3 -N 3 , ''EE'', bridging modes [12][13][14][15]), and as a tridentate bridging ligand (l 1,1,1 -N 3 [11] or l 1,1,3 -N 3 [16][17][18][19]) (Scheme 1). Both types of bidentate coordinations can mediate ferromagnetic and antiferromagnetic interactions between the metallic ions.…”
Section: Introductionmentioning
confidence: 99%
“…This ligand has attracted much attention for two main reasons. First, the azide anion can behave as a bidentate bridging ligand (end-to-on, l 1,1 -N 3 ''EO'' [9][10][11], or end-to-end, l 1,3 -N 3 , ''EE'', bridging modes [12][13][14][15]), and as a tridentate bridging ligand (l 1,1,1 -N 3 [11] or l 1,1,3 -N 3 [16][17][18][19]) (Scheme 1). Both types of bidentate coordinations can mediate ferromagnetic and antiferromagnetic interactions between the metallic ions.…”
Section: Introductionmentioning
confidence: 99%
“…The pseudohalide azide has been widely utilized not only as a versatile bridging ligand but also as an excellent magnetic coupler [2][3][4][5]. The magnetic coupling mediated through azide bridges is generally ferromagnetic in nature for the end-on (µ-1,1 or EO) mode and antiferromagnetic for the end-to-end (µ-1,3 or EE) mode [6]. For dicopper(II) complexes with the square pyramidal coordination geometry, the nature of the interaction is also strongly dependent upon the disposition of the azide bridges between metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…For dicopper(II) complexes with the square pyramidal coordination geometry, the nature of the interaction is also strongly dependent upon the disposition of the azide bridges between metal ions. For symmetric EO azido bridges, which assume a basal-basal disposition between Cu(II) ions, it has been experimentally and theoretically demonstrated that the exchange is ferromagnetic for lower Cu-N-Cu angles (<108 • ) and antiferromagnetic for higher angles, but the asymmetric EO azido bridges, which assume a basal-apical disposition, have been found to transmit interactions varying from weak ferromagnetic to medium antiferromagnetic [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In the bridging mode pattern it can act in end-on or endto-end modes, the former mode is rather less known. The azido ligand is an efficient superexchange pathway for propagating magnetic interaction between the paramagnetic centres such as copper(II), giving dimeric, tetranuclear, cubane, 1D, 2D and 3D complexes [6,7].On the other hand, a bpc dianion (2,2 0 -bipyridyl-3,3 0 -dicarboxylate) functions as a bridging ligand in a tridentate fashion through its two pyridine nitrogen atoms and one carboxylate oxygen atom [8].So far most of the coordination polymers are built with homoleptic ligands. Several examples have been reported, including the ligand combinations of terephthalate and 4,4 0 -bipy [9], carboxylate and bipyridine [10,11], pyrazine and 4,4 0 -bipy [12], oxalate and pyrazine [13], oxalate and 4,4 0 -bipy [14,15], phthalate and 4,4 0 -bipy [16], etc.…”
mentioning
confidence: 99%
“…In the bridging mode pattern it can act in end-on or endto-end modes, the former mode is rather less known. The azido ligand is an efficient superexchange pathway for propagating magnetic interaction between the paramagnetic centres such as copper(II), giving dimeric, tetranuclear, cubane, 1D, 2D and 3D complexes [6,7].…”
mentioning
confidence: 99%